(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This teaching-methodical manual is written for teachers of special education system, as well as teachers of general education schools where inclusive education has been introduced, who deal with the problems of education of deaf and hard of hearing children. Uzbek sign language and the work system for teaching it are described in detail.